MELANOMA MORBIDITY AND CAUSES OF SKIN MELANOMA ADVANCING IN THE REPUBLIC OF BASHKORTOSTAN - O. N. Lipatov; O. L. Lagno; A. M. Hanov; K. V. Menshikov; R. D. Atnabaev; R. G. Fatihov (Креативная хирургия и онкология)
The article covers the  data  of skin melanoma advancing and  of its prevalence rate  in the Republic of Bashkortostan. Clinical cases of skin melanoma advancing among residents of the Republic of Bashkortostan are described. Treatment options of the disease  are also mentioned. Causes of high skin melanoma advancing in the  Republic of Bashkortostan  in comparison with the subjects  of  Volga Federal district are considered in the article.